Increased mortality in women with cataract: a population based follow up of the North London Eye Study. Issue 4 (1st April 2002) - Reidy, A; Minassian, D C; Desai, P; Vafidis, G; Joseph, J; Farrow, S; Connolly, A
Abstract : Background/aims: In diabetics, cataract is associated with higher risk of death. In non-diabetics the data are conflicting, but some indicate an association between one type of cataract (nuclear) and increased mortality. The aim of this study was to estimate and compare age and sex specific mortality for elderly people with and without cataract in a population based cohort. Methods: A random sample drawn from a defined population of elderly people (age 65 and older) registered with 17 general practice groups in north London formed the study cohort and were followed up for 4 years. The age and sex specific mortality from various causes was estimated and compared in those with and without cataract. Results: In non-diabetics (n=1318), cataract (lens opacity at baseline) was significantly associated with higher mortality in women. The age standardised death rate per 1000 was 39.8 and 24.8 in women with and without cataract, respectively (age adjusted hazard ratio 1.7, confidence limits 1.1 to 2.7, p=0.032). This was not the case in non-diabetic men (hazard ratio 0.9, confidence limits 0.6 to 1.5, p=0.782). The excess mortality in women with cataract was consistent for cardiovascular, respiratory, and other non-cancer causes of death. There was no association between cataract and mortality from cancer. Conclusions: This study has shown, for the first time, that cataract is associated with higher mortality in women but not in men, among the non-diabetic population. This sex effect suggests that women may be exposed to risk factors that increase both the risk of cataract and mortality, and that men may have little or no exposure to these "sex specific" factors. Possible risk factors that warrant further investigation may be those associated with some pregnancy and childbearing experience.